Spatial-temporal characteristics of agricultural economic resilience and spatial spillover effects of driving factors: evidence from provincial panel data in China - Chen, Xiaoyu; Wang, Haohan; Zhu, Xingyuan; Zhang, Xiao (Frontiers in Environmental Science, 2025)
Strengthening Agricultural Economic Resilience (AER) has become a crucial approach to ensuring food security and promoting sustainable social development, particularly in light of supply shocks such as limited resources, environmental pressures, stagnating agricultural profitability, and diminishing demographic advantages. This study examines AER across 31 Chinese provinces from 2008 to 2020, analyzing its temporal evolution and spatial distribution characteristics. Additionally, it assesses the spatial spillover effects of key driving factors using the Spatial Durbin Model (SDM). The results indicate that China’s average AER rose from 0.167 to 0.266 during the study period, showing a marked upward trend and a gradual reduction in regional disparities. Furthermore, AER exhibits a strong positive spatial correlation, with higher concentrations in the eastern and central regions, while the northeastern and western areas show lower levels. Key factors such as market scale, agricultural GDP, agricultural inputs, research and development, environmental conditions, and urbanization all shape AER. The influence of these factors on regional AER highlights the presence of spatial spillover effects. Notably, the regression coefficient for urbanization on AER is −0.001, significant at the 5% level, indicating a negative spillover effect. In contrast, Market Scale, Agriculture GDP, Agricultural Factor Inputs, and Environmental factors exhibit significant positive spillover effects, all at 5%. The positive spillover effects of other driving factors are not significant. Furthermore, these findings provide practical knowledge for policy adjustments and enhancing interregional coordination to boost AER.